PERBANDINGAN KUAT TEKAN BETON RINGAN DENGAN METODA RANCANG-CAMPUR ACI DAN DREUX-CORRISE - Ratna Widyawati (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2011)
Lightweight concrete is one of solving problems to deficiency or loss that is about the size of the dead load weight of the concrete itself. Generally, lightweight concrete has the same mix-design with normal concrete, except that coarse aggregate in lightweight concrete its density must be reduced. One of the lightweight aggregate that has been produced in bulk is ALWA (Artificial Light Weight Aggregate coarse), which is lightweight aggregate from the burning of clay. Because the aggregate is light, then the aggregate can be used as coarse aggregate in lightweight concrete mixtures for building structures. There are several kinds of lightweight concrete mix design. The purpose of this research is compare of compressive strength of lightweight concrete aggregates ALWA with the ACI Methods and Dreux-Corrise Method. Specimens consist of 15 pieces of concrete cylinders (d = 150 mm, t = 300 mm) for lightweight concrete ALWA with the ACI Method. Treatment of samples was done by soaking and aerated for 7 days. Compressive strength testing performed on specimens aged 28 days. There are 3 specimens for 3 days, 7 days and 14 days for compressive strength, and there are 6 speciments for 28 days compression test. The results showed 28 days compressive strength of Dreux-Corrise Method has increased significantly by 35.36% from 14 days compressive strength. While the concrete compressive strength of 28 days with ACI method only increased by 1.92% from 14 days compressive strength. Value of compressive strength at Dreux-Corrise method is higher than the ACI method that is equal to 16.37% in the same targeted of 24.5 MPa.